Counterimmunoelectrophoresis assay for detection of adenovirus antigen. - Mankikar, S D (1979)
A rapid, sensitive counterimmunoelectrophoresis assay was developed to detect adenovirus in stools of patients with gastroenteritis. The parameters of the assay were optimized, and its sensitivity and efficiency was examined. The assay promises to be a useful alternative to conventional techniques of cell culture isolation or electron microscopy for the detection of adenovirus in stool specimens.